Comparison of early-stage primary serous fallopian tube carcinomas and equivalent stage serous epithelial ovarian carcinomas - Huann-Cheng Horng; Chiung-Ru Lai; Wen-Hsun Chang; Kuo-Chang Wen; Yi-Jen Chen; Chi-Mou Juang; Ming-Shyen Yen; Peng-Hui Wang (Elsevier, 2014)
Objective: To investigate the outcome of patients with early-stage primary fallopian tube carcinomas (PFTC) and those of patients with equivalent-stage serous epithelial ovarian carcinomas (SEOC). Materials and methods: A balanced and matched, case-control comparison was conducted in a university-based tertiary hospital database between 1978 and 2007. All PFTC and SEOC patients were treated with complete staging surgery followed by multiagent chemotherapy. One SEOC control was matched for each PFTC patient in a very uniform manner (characteristics and treatment). Disease-free survival (DFS) and overall survival (OS) were then compared using Kaplan-Meier analysis. Results: Twenty-six paired patients were analyzed. Patients with PFTC were significantly older than the SEOC patients (58 years vs. 51 years, p = 0.001). In terms of recurrence, PFTC patients frequently had an extra-abdominal metastasis (3/4, 75%), in contrast to the SEOC patients, who did not (1/5, 20%). The 5-year DFS rate was similar in both groups (85% vs. 81%, p = 0.05), contributing to a similar OS rate (89% vs. 85%, p = 0.50). The median DFS and OS of patients with PFTC and SEOC were also similar without a statistically significant difference (125 months vs. 109 months, and 125 months vs. 122 months, respectively). Conclusion: Our study demonstrated that the survival outcome of International Federation of Gynecology and Obstetrics (FIGO) I/II PFTC patients was similar to that of FIGO I/II SEOC patients, and both groups had a >80% 5-year DFS rate after complete staging surgery, followed by multiagent chemotherapy. This finding is worthy of being investigated.